2020
DOI: 10.5937/ffr47-29244
|View full text |Cite
|
Sign up to set email alerts
|

Properties of different silage maize hybrids

Abstract: The aim of this study was to observe the properties of ten maize hybrids from Serbia including agronomic traits, lignocellulosic fibre composition and in vitro dry matter digestibility. Five yellow kernel dent hybrids and five analogue red kernel hybrids were used in this study to evaluate the agronomic traits, dry matter content of the whole plant, lignocellulosic fibre composition, ratios between different fibres, in vitro dry matter and NDF digestibility. Correlation coefficients between the investigated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The average NDF digestibility obtained in our study ranged from 6.64% (ZP 747) to 21.61% (ZP 171/8) (Figure 4). They are consistent with levels that have previously been reported by a number of studies (Nikolić et al, 2020;Barrière et al, 2018). Miller et al (2021) found that higher forage NDFD caused greater NDF and that a higher NDF diet with lower NDFD decreased milk production and dry matter intake in dairy cows.…”
Section: Figure 2 Content Of the Lignocellulosic Fibers Of The Whole ...supporting
confidence: 93%
See 1 more Smart Citation
“…The average NDF digestibility obtained in our study ranged from 6.64% (ZP 747) to 21.61% (ZP 171/8) (Figure 4). They are consistent with levels that have previously been reported by a number of studies (Nikolić et al, 2020;Barrière et al, 2018). Miller et al (2021) found that higher forage NDFD caused greater NDF and that a higher NDF diet with lower NDFD decreased milk production and dry matter intake in dairy cows.…”
Section: Figure 2 Content Of the Lignocellulosic Fibers Of The Whole ...supporting
confidence: 93%
“…85%, 13.17-15.92%, 51.43-55.57%, 43.77-48.44%, 43.85-48.71%, 90.53-110.62% and 90.40-110.46% (Table 1). These results are in agreement with those of earlier studies by Nikolić et al (2020), Milašinović-Šeremešić et al (2017, and Khan et al (2015). The ADF/NDF ratio is used for the prediction of the concentration of indigestible NDF (iNDF) (Koukolová et al, 2004).…”
Section: Figure 2 Content Of the Lignocellulosic Fibers Of The Whole ...supporting
confidence: 91%
“…Acid detergent fiber (ADF) primarily consists of cellulose, indigestible lignin and inorganic silica and is negatively correlated with the digestibility of forages. Animals tend to consume less forage as the content of NDF increases (Bittman, 2004;Nikolić et al, 2020a).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted at the Maize Research Institute determined that the high content of both digestible and metabolic energies indicated that DDGS samples obtained after bioethanol production from maize hybrids grain can be classified as both protein and high-energy feeds and can be used for the preparation of feed for different types and categories of farm animals (Nikolić et al, 2020a;Semenčenko et al, 2015;Semenčenko et al, 2014;Semenčenko, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if there can be a reduction in feed formulation costs, it compensates for the economic loss associated with higher feed use per unit of production (Goda et al, 2020 a, b). Recently, studies have shown that the use of DDGS in aquafeed formulations decreases feed ingredient costs for fish in the amount of 14% of the total revenues from bioethanol production (Nikolić et al, 2020 a;Sándor et al, , 2021Oliveira et al, 2020), because feed formulations using DDGS in aquafeeds are less expensive compared to other commercial feeds, which is reflected in higher yield per unit (Sándor et al, 2021 a, b). The economic benefit of including DDGS in carp feeds was demonstrated by significantly increasing per-hectare profit and benefit-cost ratio, which are attributed to higher yields, improved feed conversion, and lower cost of novel feed formulation (Sándor et al, 2021 a).…”
Section: Economic Contribution Of Ddgs On Feedsmentioning
confidence: 99%